Analysis of Menopausal Hormone Therapy to Chinese Patients with Menopausal Syndrome: A Real-World Retrospective Study from Chinese Hospitals - Zhu Z; Shi A; Liu L; Jin G; Wang X (Drug Design, Development and Therapy)
Zhenling Zhu,1 Aiping Shi,1 Lanhua Liu,2 Guixiu Jin,2 Xianli Wang3 1Department of Pharmacy, Taixing People’s Hospital Affiliated to Yangzhou University, Jiangsu, Taixing, 225400, People’s Republic of China; 2Department of Obstetrics and Gynecology, Taixing People’s Hospital Affiliated to Yangzhou University, Jiangsu, Taixing, 225400, People’s Republic of China; 3Department of Pharmacy, Obstetrics and Gynecology Hospital of Fudan University, Shanghai, 200011, People’s Republic of ChinaCorrespondence: Xianli Wang, Obstetrics and Gynecology Hospital of Fudan University, 419 Fangxie Road, Huangpu District, Shanghai, 200011, People’s Republic of China, Email wangxianli1691@fckyy.org.cnPurpose: To investigate and analyse the changing trends in the use of menopausal hormone therapy (MHT) for patients with menopausal syndrome (MPS) in hospitals in nine Chinese cities from 2019 to 2023 and to provide an evidence base for the rational clinical use of MHT.Methods: Data on the use of MHT by patients with menopausal syndrome were collected and a trend analysis was conducted, including trends in the number of prescriptions, patient age, total prescription amount, average prescription amount, defined daily doses (DDDs), defined daily cost (DDC), and drug rank ratio (B/A).Results: From 2019 to 2023, the prescriptions of MPS patient were concentrated in East China and North China, with an average age of 48.22± 5.94 years. In a span of five years, the number of prescriptions increased by 86.08%, the total prescription amount increased by 126.58%, and the average prescription amount increased by 21.76%. The B/A ratios for estradiol/estradiol dydrogesterone and tibolone were both determined to be 1, thus indicating that the sales amounts and DDDs of these two drugs were in good agreement and that the drug costs are reasonable.Conclusion: From 2019 to 2023, the number of MPS patients and the total number of treatment drug prescriptions in nine cities throughout the country demonstrated an increasing trend. The estradiol/estradiol dydrogesterone and tibolone were the main sex hormone drugs that were used to treat MPS. The state’s abolition of the drug price addition policy and the organization of centralized drug procurement in some areas had alleviated the financial burdens on patients to a certain extent.Keywords: menopausal syndrome, menopausal hormone therapy, estradiol/estradiol dydrogesterone, tibolone